Engineering Mechanics: adoption of project-based learning supported by computer-aided online adaptive assessments - overcoming fundamental issues with a fundamental subject - Balash, Cheslav; Richardson, Steven; Guzzomi, Ferdinando; Rassau, Alex (European journal of engineering education, 2020)
Engineering Mechanics is widely acknowledged in the literature as a subject where students experience great difficulty in understanding and applying threshold concepts, which often results in high failure rates. To address this, we introduced two new complementary assessments: a practical design project and a series of adaptive online tutorials with an assessed component to motivate regular participation. Feedback from students regarding the design project suggested that they found it an effective activity to motivate engagement with the subject material and to gain appreciation of its applicability to real-world problems. The level of successful engagement with online tutorials showed a high correlation with examination success. The mean final examination mark was 60% and 62% in 2017 and 2018, respectively, following the introduction of the amended assessment regime, compared to 32% in 2016.